Cyrtodactylus tahuna sp. nov., a new bent-toed gecko (Reptilia: Squamata: Gekkonidae) from Sangihe Island, North Sulawesi, Indonesia - Riyanto, Awal; Arida, Evy; Koch, André (Zootaxa, 2018)
Cyrtodactylus tahuna sp. nov. is a new bent-toed gecko we describe herein based on three specimens from Sangihe, North Sulawesi, Indonesia, an island situated in the northern corner of the Wallacea biodiversity hotspot. The new species is a medium sized Cyrtodactylus with a SVL of up to 78.5 mm in adult males and 79.2 mm in females. It is easily distinguished from all but four species (Cyrtodactylus fumosus, C. halmahericus, C. papuensis, and C. tambora) occurring on Sulawesi as well as in the Moluccas and the Lesser Sunda Islands, by possessing precloacal and femoral pores, enlarged precloacal and femoral scales, and lacking transversely enlarged median subcaudal scales. It differs from C. fumosus by the presence of tubercles on the ventrolateral fold, more unkeeled dorsal tubercles (19 versus 4–7) and a pit-like precloacal depression in males (versus groove in males); from C. halmahericus by presence of smaller scales between the enlarged precloacal and femoral scales (versus a continuous series of enlarged precloacofemoral scales) and a continuous series of precloacofemoral pores, as well as the presence of a pit-like precloacal depression in male (versus groove in males), from C. papuensis by possessing a pit-like precloacal depression in males (versus a groove ); and from C. tambora by the presence of tubercles on the dorsal surface of the brachium and the possession of femoral pores. Our contribution, along with several other recent descriptions of bent-toad geckos from Southeast Asia, clearly indicating that the diversity of the genus Cyrtodactylus in Indonesia is still underestimated.